The Evalution Of Acetyl-11-Keto-Beta-Boswellic Acid (AKBA)- On Induced Autism In A Mice Model (International Journal of Environmental Sciences, 2025)
Background: Autism spectrum disorder (ASD), a neurodevelopmental condition, is characterized by difficulties in social interaction and communication that manifest in early childhood. The only authorized medications for the treatment of ASD are risperidone and aripiprazole. Objectives: The research aims to demonstrate the possible therapeutic effects of acetyl-11-keto-beta-boswellic acid on an induced offspring model of autism. Additionally, to assess the influence of AKBA on interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α). Materials and Methods: We induced the condition in mice by injecting sodium valproate (600 mg/kg) to pregnant mice. Prenatal sodium valproate-exposed mice were divided into four distinct groups: two experimental groups received AKBA (5mg/kg and 15mg/kg) and risperidone (1mg/kg), while a control group was administered normal saline. Behavioral tests, including social interaction tests, were segmented into three phases: habituation, familiarization, and testing, each lasting 10 minutes, and were performed on postnatal day 65. Additionally, assessments of anti-inflammatory markers such as TNF-α and IL-6 were done on postnatal day 66. Results: The study showed AKBA markedly enhanced behavioral abnormalities related to social communication and reduced neuro-inflammation in the brain. AKBA treatment significantly improved the cognitive performance of ASD mice via modulating neurogenesis, likely linked to the potent antioxidant and anti-inflammatory properties of AKBA. Conclusion: AKBA had significant anxiolytic and anti-inflammatory effects that enhanced behavioral activity in the mice. These data indicate that AKBA may represent a viable therapeutic option for persons with ASD.